2015
DOI: 10.1155/2015/601083
|View full text |Cite
|
Sign up to set email alerts
|

Flurbiprofen Axetil Enhances Analgesic Effects of Sufentanil and Attenuates Postoperative Emergence Agitation and Systemic Proinflammation in Patients Undergoing Tangential Excision Surgery

Abstract: Objective. Our present study tested whether flurbiprofen axetil could reduce perioperative sufentanil consumption and provide postoperative analgesia with decrease in emergency agitation and systemic proinflammatory cytokines release. Methods. Ninety patients undergoing tangential excision surgery were randomly assigned to three groups: (1) preoperative dose of 100 mg flurbiprofen axetil and a postoperative dose of 2 μg/kg sufentanil and 10 mL placebo by patient-controlled analgesia (PCA) pump, (2) preoperativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 28 publications
1
18
0
Order By: Relevance
“…Though some clinical studies have conflicting results regarding the efficacy of preemptive analgesia, [ 16 ] similar to other studies, [ 7 , 9 ] our present study suggested preoperative administration of FA and CX had preemptive analgesia effects. Researchers argue that almost all the analgesic studies were published by anesthetists, and some important details usually considered by orthopedics, such as surgical approach, technique of incision, and type of implant were not reported in those papers.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Though some clinical studies have conflicting results regarding the efficacy of preemptive analgesia, [ 16 ] similar to other studies, [ 7 , 9 ] our present study suggested preoperative administration of FA and CX had preemptive analgesia effects. Researchers argue that almost all the analgesic studies were published by anesthetists, and some important details usually considered by orthopedics, such as surgical approach, technique of incision, and type of implant were not reported in those papers.…”
Section: Discussionsupporting
confidence: 87%
“…[ 5 8 ] Flurbiprofen axetil (FA), which is incorporated in lipid microspheres, is a NSAID with high affinity to the site of surgical incision. [ 9 ] Celecoxib (CX) is a selective cyclooxygenase-2 (COX-2) inhibitor shown to be as effective as traditional NSAIDs as an analgesic for acute postoperative pain and has fewer gastrointestinal side effects than traditional NSAIDs. [ 7 ] There are a few reports compare the effectiveness of preoperative flurbiprofen axetil and celecoxib on postoperative analgesic and perioperative opioid consumption after TKA.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, sufentanil with flurbiprofen as an alternative multimodal analgesia for postoperative pain control was given as a loading dose for PCA at the end of surgery. Studies have shown that postoperative analgesia with opioid plus flurbiprofen resulted in lower pain scores, 36 , 37 thus, this strategy of multimodal postoperative analgesia was applied in this study. Even though the routine use of PCA with a background infusion is not recommended, it remains suitable in patients after thoracotomy who require high opioid consumption or complain of waking due to severe pain at night.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that parecoxib sodium, a nonsteroidal anti-inflammatory drug (NSAID) and selective cyclooxygenase (COX)-2 inhibitor commonly used for postoperative analgesia, reduced the incidence of POD in elderly patients (Mu et al, 2006). Flurbiprofen axetil, another potent NSAID and nonselective COX inhibitor, was used for postoperative analgesia and reduced postoperative opioid consumption (Geng et al, 2015). Administration of flurbiprofen axetil was proved to reduce inflammatory responses and induce neuroprotective effects (Wang et al, 2008;Xu, Tan, Chen, Lou, & Chen, 2008).…”
mentioning
confidence: 99%